Human Rights Dimensions in Climate Chamge: Synergies and Caveats - Auz Vaca, Juan (2017)
Climate change poses serious threats to the enjoyment of human rights around the world, particularly for the most vulnerable members of society; hence, states have positive and negative duties when safeguarding substantive and procedural rights in this context. However, there are several legal challenges when human rights law is used to address the effects of climate change. Said challenges are mostly tangible, not only for climate change-related cases in domestic and regional human rights law situations, but also as regards climate change mitigation measures as a potential threat to human rights. KEYWORDS: Climate Change, Human Rights, Environmental Law, regional regulation, regulation. JEL CODE: Q54, J21